The Development of Cybersecurity Information Sharing Framework for National Critical Information Infrastructure in Indonesia - Farouq Aferudin; Kalamullah Ramli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The increase of cyber attacks in the Critical Information Infrastructure (CII) requires every organization to collaborate through Cybersecurity Information Sharing (CIS). To support the implementation of the CIS, governance support is needed in the form of a framework that can be used as a reference. This study focuses on developing a CIS framework for the CII sector in Indonesia which consists of three main outputs, namely the proposed ecosystem, the proposed framework and the recommendations for the implementation of the framework. The proposed framework is based on standards including ISO/IEC 27032, NIST SP 800-150 and ENISA ISAC in a Box, based on best practices for implementing CIS and best practices for implementation in other countries including the United States, Australia, United Kingdom, Singapore and Canada. To validate, the expert judgment method was used to obtain suggestions for improvement. The expert judgment method was also carried out quantitatively to measure interrater reliability between experts using Fleiss Kappa Statistics. The measurement results show a kappa value of 0.938, which means that the proposed framework implementation recommendation gets an agreement from the experts at the almost perfect agreement level.